Review on computational strategies for bi-layered metal powder compaction - Mohd Tahir, Suraya; Mohd Yusoff, Syamimi; Mohamed Ariff, Azmah Hanim; Supeni, Eris Elliandy; Anuar, Mohd Shamsul (Elsevier, 2024)
Development on materials is vital for modern appliances through inventiveness of experimental process, analyzation and optimization encompassing association of its investigated sub-materials. Admittedly, computational strategies are relevant to this highly demand-products. Therefore, this paper provides an outline for the modeling approach involving two layers of metal-based compressed powder through Powder Metallurgy (PM) route to sustenance the existence of virtual step solutions. Throughout this review, many researches exhibited great success in validating modeling work to their experimental findings concerning on metal-metal, metal-ceramic and metal-composites bilayers. Analysis on green powder compact is crucial to be confront owing to the fact that the finished mechanical properties was a post-property from its earlier formed. A scrutinize part is the implementation of algorithm to describe powder behavior under double loading as well as to relate with other mechanical variables that eventually require expertise on computational plasticity knowledges involving horizontal contacts. Apart from visualization tasks, frequent surveillance from their characterization works were equally troublesome as finding alternative yet reliable method to analyze the distribution is essential for un-sintered powder compact. With the establishment of this comparison, further production on bilayer samples can be done conveniently, thus more robust samples can be provided with minimum of defects.